2018
DOI: 10.1021/acs.jpcb.7b11051
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Fractional Analysis of Molecular Diffusion in Polymer Multilayers by FRAP: A New Simulation-Based Approach

Abstract: Comprehensive analysis of the multifractional molecular diffusion provides a deeper understanding of the diffusion phenomenon in the fields of material science, molecular and cell biology, advanced biomaterials, etc. Fluorescence recovery after photobleaching (FRAP) is commonly employed to probe the molecular diffusion. Despite FRAP being a very popular method, it is not easy to assess multifractional molecular diffusion due to limited possibilities of approaches for analysis. Here we present a novel simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
(63 reference statements)
1
16
0
Order By: Relevance
“…In regards to this, the LbL assembly will provide a strong tool for introduction of various components into the assembled structures in order to tune a function of the finally-assembled structure. Novel approaches to probe diffusion into the formed multilayers are essential to understand and control a structure of the assemblies and release characteristics of BACs from the assembled structures [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…In regards to this, the LbL assembly will provide a strong tool for introduction of various components into the assembled structures in order to tune a function of the finally-assembled structure. Novel approaches to probe diffusion into the formed multilayers are essential to understand and control a structure of the assemblies and release characteristics of BACs from the assembled structures [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…In further studies, this approach was mainly applied for studying the diffusion of proteins in HA/PLL PEMs [ 108 , 109 , 110 ]. It was found that, similarly to the polymers that comprise PEMs, proteins loaded into PEMs also represent several fractions that have different degree of the binding to polymer network and therefore have different diffusivity ( Figure 4 B) [ 109 ].…”
Section: Analysis Of Polymer Dynamics Inside Pems: Methodsmentioning
confidence: 99%
“…Figure taken from reference [ 108 ], Copyright © 2020 Elsevier Ltd. ( B ) Distribution of diffusion coefficients of CytC loaded into (HA/PLL) 24 multilayers, where 24 is the number of polymer bilayers. Figure taken from reference [ 109 ], Copyright © 2020 American Chemical Society ( ).…”
Section: Figurementioning
confidence: 99%
“…Research activities in the area of LbL include planar films (Von Klitzing, 2006; Selin et al, 2018) and capsules. In addition to nanometer-thin LbL films, so-called micrometer thick exponentially grown LbL films were developed (Lavalle et al, 2004), which can host an enormous amount of both small and high molecular weight substances due to a large thickness of multilayers, e.g., those made of biopolymers (Sustr et al, 2015, 2018; Velk et al, 2016; Vikulina et al, 2016; Prokopovic et al, 2017). The uptake of the molecules, with various natures, is driven by the molecule interaction with free (uncompensated) charges of the inter-polymer complexes in the multilayers.…”
Section: Organic Chemical Matricesmentioning
confidence: 99%